Multiscale interfacial enhancement of surface grown carbon nanotubes carbon fiber composites. Issue 5 (13th February 2023) - Li, Min; Xing, Fei; Li, Tianshu; Wang, Shaokai; Gu, Yizhuo; Zhang, Wei; Wang, Yanjie; Li, Qinghui
Abstract: The interface properties between surface grown carbon nanotubes carbon fiber (CNTs‐CF) and epoxy resin were investigated by different modification methods. The X‐ray photoelectron spectrometer probations show that the pristine CNTs‐CF has very low contents of both oxygen element and active carbon element. Taking the naked carbon fiber (CF) without CNTs grown as a reference, the interfacial shear strength (IFSS) of CNTs‐CF/epoxy is only 5.6% higher. After heat treatment, chemical modification and sizing treatments, the surface chemical activity of CNTs‐CF is improved considerably. In contrast with the IFSS of standard CF/epoxy, the interfacial strength of chemical‐treated CNTs‐CF‐E1/epoxy is increased to 122.8 MPa by 29.7%. The increasing content of the epoxy active groups at the modified CNTs‐CF‐E1 surface is conducive to forming covalent bonds between the epoxy resin and the CNTs‐CF‐E1 surface particularly the activated nanotube surface. The enhancement of CNT/epoxy interface is beneficial to the over whole interface property of the composites. Hence, the compressive and torsion strength of sizing CNTs‐CF‐E1 bundle combined with epoxy resin are increased by 32.4% and 14.1%, respectively. The SEM images show the failure morphologies of different modification methods, and the enhancement mechanism of multiscale interface is further clarified. Compared with chemical treatment, heat treatment can remove the inert amorphous carbon on the CNTs‐CF fiber surface and improve the interface adhesion of CNT/epoxy and CF/epoxy, and surface sizing treatment improves the CF/epoxy interface. The enhancement mechanisms of these modified CNTs‐CFs/epoxy should be ascribed to the competition and synergetic effects of the multiscale interfaces, including CNT/CF, CNT/epoxy, and CF/epoxy. Abstract :